2010
DOI: 10.1111/j.1460-9592.2010.03281.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond pain: predictors of postoperative maladaptive behavior change in children

Abstract: Individual child factors above and beyond pain predict maladaptive postoperative behavior change; identification of these predictors may be helpful in both preventing and ameliorating difficulties with behavioral recovery following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 37 publications
(47 reference statements)
7
91
0
1
Order By: Relevance
“…The effects of anesthetic neurotoxicity are also unlikely to manifest immediately, while post-operative maladaptive behaviors, which are present in one third of children 2 weeks after surgery, may resemble a variety of different mental disorders. (28) In order to avoid capturing pre-existing diagnoses and cases of transient post-operative maladaptive behaviors, as well as reduce ascertainment bias due to increased medical visits in children immediately after surgery, a latency period of at least 6 months was imposed on the definition of anesthetic related incident mental disorders. Therefore, all exposed children with a mental disorder diagnosed prior to surgery, or in the first 6 months after the surgical procedure were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of anesthetic neurotoxicity are also unlikely to manifest immediately, while post-operative maladaptive behaviors, which are present in one third of children 2 weeks after surgery, may resemble a variety of different mental disorders. (28) In order to avoid capturing pre-existing diagnoses and cases of transient post-operative maladaptive behaviors, as well as reduce ascertainment bias due to increased medical visits in children immediately after surgery, a latency period of at least 6 months was imposed on the definition of anesthetic related incident mental disorders. Therefore, all exposed children with a mental disorder diagnosed prior to surgery, or in the first 6 months after the surgical procedure were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, high doses of opioids may cause undesirable adverse effects, such as respiratory depression, oxygen desaturation, nausea, vomiting, and postoperative negative behavioral changes (PNCs). [2][3][4] Thoracic paravertebral block (TPVB) is used as an alternative method to epidural anesthesia/analgesia to provide postoperative analgesia for thoracic surgery in adults. [5][6][7] The mechanism of action of paravertebral block involves local anesthetic (LA) penetration into the spinal nerve to produce an afferent sensory blockade.…”
mentioning
confidence: 99%
“…In genitourinary surgery, that number was even higher. 19 Fortier et al 20 found 81% of children with NPOBC at POD 1, and about 35% in the second week. These results seem comparable with the results of our study.…”
Section: Discussionmentioning
confidence: 97%
“…They include potential interactions between preoperative (anxiety of child and parents, a child's temper, preparation for surgery), intraoperative (anaesthesia induction technique, selection of anaesthetic drugs) and postoperative factors (ED, pain, unfamiliar hospital environment). 20,[23][24][25] Initial research by Kain et al 1 found no correlation between pain and NPOBC. In contrast, pain mainly after hospitalisation is one of the biggest risk factors for the occurrence of behaviour changes after surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation